Assessment of different drill diameter on bone drilling process - Fernandes, M.G.A. (2018)
Drilling is a highly demanding machining process due to drill bit geometries complexity and the progressive material failure on the workpiece. When applied to living tissues the process assumes greater attention to ensure a minimally invasive procedure. Implant failure may occur as result of the mechanical conditions created around the hole. Simulation of bone drilling could be used as methodology to optimize the process and parameters in order to reduce the bone damage and ensure ideal drilling conditions. In this research, the effect of drill bit diameter on the generated stresses level during drilling was analysed through numerical simulations and compared with experimental results. An explicit dynamic program was used in the simulations of three dimensional elasto-plastic dynamic finite element models. The numerical models were validated with drilling experiments on polyurethane foam materials with similar properties to the human cortical bone. The results indicated that smaller drill bit diameter leads to a decrease in the stress in foam materials for a constant feed-rate and drill speed. The maximum stress occurred in the drilled zone and surrounding tissues.